Energy storage participation for frequency regulation of microgrid in PV-dominated power system - Singh, Nirdesh; Jain, Dinesh Kumar (International Journal of Applied Power Engineering (IJAPE), 2025)
The frequency stability of a power grid is effectively managed through the inertia and power reserves supplied by synchronous generators. Due to increasing concerns about the greenhouse effect and global warming, renewable energy sources (or microgrids) are increasingly replacing traditional fossil fuel-based methods of electricity generation. As microgrid deployment proliferates, power systems' inherent complexity and non-linear dynamics have escalated, rendering conventional controllers inadequate across diverse operating conditions. Factors such as reduced energy inertia, heightened penetration of renewable energy sources, and significant power fluctuations within confined transmission systems have heightened the vulnerability of microgrid frequencies to instability. This paper elucidates the concept of microgrids, examines frequency fluctuations in the presence of solar and diesel generators alongside load variations, and presents simulation-based analyses. Moreover, it provides a succinct overview of frequency control methodologies. Validation outcomes demonstrate the efficacy of the proposed controller in maintaining system frequency amidst fluctuating load demands and renewable energy inputs.